High-performance CoII-phthalocyanine-based polymer for practical heterogeneous electrochemical reduction of carbon dioxide. (20th January 2021) - Luangchaiyaporn, Jirapong; Wielend, Dominik; Solonenko, Dmytro; Seelajaroen, Hathaichanok; Gasiorowski, Jacek; Monecke, Manuel; Salvan, Georgeta; Zahn, Dietrich R.T.; Sariciftci, Niyazi Serdar; Thamyongkit, Patchanita
Highlights: Bithiophene-functionalized Co II -phthalocyanine can be readily electropolymerized. The polymer exhibits high catalytic activity for selective conversion of CO2 to CO. CO2 reduction can be achieved at low overpotential under ambient aqueous condition. Spectroelectrochemical study suggests Co I -centered catalytic mechanism. Abstract: A new bithiophenyl-substituted Co II -phthalocyanine is synthesized and electropolymerized to obtain corresponding polymer films on an indium tin oxide-coated glass and a carbon paper. Formation of the target polymer on substrates is confirmed by Ultraviolet–visible spectrophotometry, Raman spectroscopy and attenuated total reflection-Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy analysis, scanning electron microscopy and energy dispersive X-ray spectroscopy. Heterogeneous electrochemical reduction of carbon dioxide (CO2 ) in a 0.5 M KHCO3 aqueous solution under catalysis of the target polymer coated on the carbon paper gives carbon monoxide (CO) as a major product. Controlled potential electrolysis at a constant potential of –0.66 V vs. reversible hydrogen electrode, corresponding an overpotential of –0.54 V from thermodynamic potential for CO production, for 2 h leads to optimum yield of CO with Faradaic efficiency (FE), turnover number (TON) and turnover frequency (TOF) of 94%, 2.10 × 10 3 and 0.29 s –1, respectively. Upon 20-h electrolysis with quantitative product monitoring, the target polymer appears to be stable throughout the process and continuously produces CO with the FE, TON and TOF of 72%, 1.24 × 10 4 and 0.17 s –1, respectively. Spectroelectrochemical study suggests metal-centered mechanism via formation of active reduced species having significant interaction of Co I with CO2 . This research demonstrates the use of the synthetically practical Co II -phthalocyanine-based polymeric material as an efficient and stable electrocatalyst for the CO2 reduction. Graphical abstract: Image, graphical abstract